2013
DOI: 10.1002/jcb.24667
|View full text |Cite
|
Sign up to set email alerts
|

STRESS‐Responsive Deacetylase SIRT3 is Up‐Regulated by Areca Nut Extract‐Induced Oxidative Stress in Human Oral Keratinocytes

Abstract: Areca chewing is an important environmental risk factor for development of oral premalignant lesions and cancer. Epidemiological evidence indicates that areca chewing is tightly linked to oral carcinogenesis. However, the pathogenetic impacts of areca nut extract (ANE) on normal human oral keratinocytes (HOKs) are unclear and possibly involve oxidative stress via redox imbalance. Sirtuin 3 (SIRT3) is a member of the sirtuin family of proteins that play an important role in regulating cellular reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…In addition, co‐treatment with NAC, Trolox, and penicillamine could prevent ARNO‐induced ROS production in the same cell line (Figures ). In fact, similar results have been reported by others . They show that both arecoline and areca nut extract increase ROS production in various cell lines and this effect can be effectively attenuated by antioxidants, including catalase, NAC, and glutathione.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, co‐treatment with NAC, Trolox, and penicillamine could prevent ARNO‐induced ROS production in the same cell line (Figures ). In fact, similar results have been reported by others . They show that both arecoline and areca nut extract increase ROS production in various cell lines and this effect can be effectively attenuated by antioxidants, including catalase, NAC, and glutathione.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, similar results have been reported by others. 27,36,40 They show that both arecoline and areca nut extract increase ROS production in various cell lines and this effect can be effectively attenuated by antioxidants, including catalase, NAC, and glutathione. In general, a buildup of ROS in cells may cause damage to DNA, RNA, and proteins, and may cause cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics research has shown that several subunits of the enzymes in the mitochondrial ETC and TCA cycle have multiple acetylation modification sites, and increased acetylation was observed in Sirt3 −/− tissues, indicating that the enzyme activities may be regulated by Sirt3. 27 , 28 , 29 In addition, mice lacking Sirt3 showed striking hyperacetylation of mitochondrial proteins, which were associated with accelerated development of metabolic syndrome. 30 , 31 , 32 Our current findings suggested that RSV promotes SOD2 deacetylation in mitochondria, which was suppressed by Sirt3 siRNA transfection, suggesting that Sirt3 plays a critical role in RSV-induced deacetylation in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte differentiation is known to influence the formation/maintenance of the protective skin barrier (Bause et al ., ; Chen et al ., ). However, dysregulation in the balance of ROS homeostasis is known to impact keratinocyte differentiation.…”
Section: Molecular Functions Of Sirt3mentioning
confidence: 97%